Internationalization of Chinese open universities - Songyan Hou (AAOU Journal, 2022)
Purpose - In 2019, the goal of developing a world-class open university through different stages was put forward by the Open University of China (OUC), which indicated that internationalization for Chinese open universities came to the agenda. However, international activities of open universities are different from those in conventional universities, and how to fulfill the goal of internationalization is a main issue faced by educators in Chinese open and distance education arena. This research aimed to identify ways of internationalization for the OUC system.